Effectiveness of Knotless Suture as A Wound Closure Agent for Impacted Third Molar - Kumar, Naresh; Ali, Anwar; Bai, Tivishna; ., Kiran; Ram, Gobind; Zulfiqar, Roma (Biological and Clinical Sciences Research Journal, 2025)
Impacted third molar extraction is a common surgical procedure performed by oral and maxillofacial surgeons, often requiring effective wound closure techniques. Conventional sutures have been widely used; however, knotless sutures have emerged as an alternative method, potentially offering faster wound closure and reduced post-operative complications. This study evaluates the effectiveness of knotless sutures as a wound closure agent compared to conventional sutures in impacted third-molar surgeries in the Pakistani population. Objective: To compare the outcomes of knotless sutures versus conventional sutures regarding wound closure time and post-operative swelling in impacted third-molar surgeries. Methods: A randomized controlled trial was conducted at the Department of Oral & Maxillofacial Surgery, Dr. Ishrat Ul Ebad Institute of Oral Health Sciences, Dow University of Health Sciences, Karachi, Pakistan. 72 patients undergoing impacted third molar extraction were randomly allocated into Group A (knotless sutures) and Group B (conventional sutures), with 36 patients in each group. Primary outcomes included wound closure time (measured in minutes) and post-operative swelling (measured in millimeters) at 1-hour and 72-hour intervals. Data were analyzed using SPSS version 23, and statistical significance was set at p≤0.05. Results: The mean age of participants was 26.14 ± 4.66 years in Group A and 24.50 ± 4.39 years in Group B. Mean wound closure time in Group A was significantly lower (2.78 ± 0.90 minutes) compared to Group B (4.47 ± 1.30 minutes, p=0.0001). Swelling at 1 hour post-operatively was significantly lower in Group A (42.69 ± 4.82 mm) than in Group B (46.22 ± 4.46 mm, p=0.002). Similarly, at 72 hours, swelling was lower in Group A (34.75 ± 4.80 mm) compared to Group B (40.80 ± 6.56 mm, p=0.0001). Conclusion: Knotless sutures improved wound closure efficiency and reduced post-operative swelling compared to conventional sutures in impacted third-molar surgeries. These findings support adopting knotless suturing techniques in oral surgical procedures to enhance clinical outcomes and patient comfort.